Pharmacotherapy of Anorexia Nervosa and Bulimia Nervosa Using SSRIs, MAOIs and TCAs - Sanil, Sripriya (Indian Journal of Pharmaceutical Education and Research, 2025)
Abstract Anorexia nervosa and bulimia nervosa are mental disorders categorised under eating and feeding disorders (American Psychiatric Association). While psychotherapy is the main form of treatment, pharmacotherapy can also be used for these disorders. This paper discusses the use of Selective Serotonin Reuptake Inhibitors (SSRIs), Monoamine Oxidase Inhibitors (MAOIs) and Tricyclic Antidepressants (TCAs) in treating anorexia nervosa and bulimia nervosa. Studies found in the database provided by Web of Science were reviewed and relevant English language and translated studies were considered. SSRIs have limited effect on anorexia nervosa and require further research to ascertain their efficacy. SSRIs such as fluoxetine, sertraline, citalopram, and fluvoxamine are effective in treating bulimia nervosa. Monoamine oxidase inhibitors and tricyclic antidepressants cannot be used to treat anorexia nervosa since they are not safe to use for this specific eating disorder. In some cases, a number of MAOIs (moclobemide, phenelzine, tranylcypromine and isocarboxazid) are effective in treating bulimia nervosa alongside some TCAs (nortriptyline, imipramine, desipramine and amitriptyline). Anorexia nervosa and bulimia nervosa are both conditions with high mortality rates and it is vital to understand more about the different forms of treatment that can be employed to cure these disorders. SSRIs are to be used as the first treatment but there is a possibility of response to MAOIs and TCAs from treatment resistant patients.
Keywords: Anorexia Nervosa; Bulimia Nervosa; Selective Serotonin Reuptake Inhibitors; Monoamine Oxidase Inhibitors; Tricyclic Antidepressants